Screening of bacteria in Yarık Sinkhole, Antalya, Turkey for carbonate dissolution, biomineralization and biotechnological potentials - Arslan- Aydoğdu, Elif Özlem; Avci, Yağmur; Ahamada Rachid, Nahdhoit; Çolak, Batu; Doğruöz-Güngör, Nihal (Acta Carsologica, 2023)
Abiotic and biotic factors, especially microorganisms, play a role in the development of cave formations and the existence of unique characteristics of each cave. Due to the ecological conditions that characterize the cave environments, highly specialized microorganisms that are the main source of diverse bioactive compounds, inhabit these environments. The aim of this study is to determine the role and biotechnological potential of the bacteria isolated from Yarık Sinkhole located in Antalya (Turkey) by screening their ability to induce the CaCO3 precipitation, to hydrolyze urea, to induce calcite dissolution, and screening their possession of NRPS/PKS gene clusters. The most prevalent phylum is the Bacillota (synonym Firmicutes) (75.7 %), while the dominant species is Bacillus pumilus (33 %). All the isolates showed crystal formation on B4 agar medium, and the Energy dispersive X-Ray spectroscopy (EDS) analyses showed that the crystals are predominately composed of calcium, carbon and oxygen. Ninety-six (96 %) of our isolates have negative ureolytic activity. According to this result and having the ability to induce the CaCO3 precipitation, bacteria in this environment use other biosynthesis pathways than urea hydrolysis. MgCO3 and CaCO3 were dissolved by 61 % and 59 % of the isolates, respectively. In addition, 5.9 % and 53.7 % of the isolates showed the possession of PKS and NRPS genes, respectively. This result reveals that our isolates have high industrial and biotechnological potential. They may constitute good candidates for further biotechnological applications such as construction of bio-concretes, bioremediation, soil fertility, and production of biologically active secondary metabolites.